Metalated Hexaphyrins: From Understanding to Rational Design. Issue 49 (14th October 2015) - Alonso, Mercedes; Pinter, Balazs; Geerlings, Paul; De Proft, Frank
Abstract: The heretofore unpredictable behavior of [26] and [28]hexaphyrins upon metalation has been elucidated through quantum chemical calculations. It is demonstrated that the molecular topology of Group 10 and Group 11 metal complexes of hexaphyrins depends on sensitive interplay between the intrinsic ligand strain and the metal–ligand interaction strength. As such, the aromaticity of the ligand and effective charge of the metal are revealed as key factors determining the binding mode and the preference for Möbius or Hückel structures. These findings offer a new perspective to rationalize experimental observations for metalated hexaphyrins. More importantly, the proposed guidelines could be useful for designing novel complexes of hexaphyrins, such as a hitherto unknown Möbius [26]hexaphyrin complex. Abstract : The unpredictable behavior of [26]‐ and [28]hexaphyrins upon metalation has been elucidated through quantum chemical calculations. Aromaticity and effective charge of the d 8 metals are revealed as key factors determining the binding mode and the preference for Möbius or Hückel structures of metalated hexaphyrins. Reducing the effective charge of the d 8 metal enhances the conformational stability of chiral Möbius complexes of hexaphyrins with a CNNN binding mode.